Positive Politeness Strategies Analysis in the Court Situation: Caught in Providence YouTube’s Video Welcome to America - Mawaddah, Tiar Aulia; Cahyono, Setyo Prasiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Politeness strategies are the ways that used by someone to convey their speech when having a conversation with others [Saputra, Lubis, Setiawan, 2021]. Politeness strategies can be observed in everyday’s life also in similar circumstances but in different situations, namely in the judicial process. This study aims to find and examine positive politeness strategies used by the judge and the defendant in court room entitled “Welcome to America!”. In this study, the researchers apply qualitative method by describing the phenomenon of the data. The source of the data in this study was gained from a YouTube channel account “Caught in Providence”.